Pembacaan Kontemporer Al-Qur`an Muhammad Syahrur; Batas Minimal dan Maksimal Aurat Wanita - Nihayatul Husna (LPPM IAINU Kebumen, 2021)
Muhammad Syahrur is one of the Islamic thinkers contemporary who shouted the need for renewal and review Islamic thought. Syahrur limited himself to contemporary readings only to the text of the Scriptures. Contemporary reading offered by Syahrur is an attempt to see and study the Bible with a scientific approach (scientific) which is heavily influenced by the positivistic paradigm. The purpose of this research to fin and analyze Syahrur's views on the Qur'an. Writing This belongs to library research whose data collection techniques carried out through literature studies and data analysis using the content method analysis. The main source of this writing is the works of Syahrur. Discussion result shows that Syahrur's contemporary reading of the textuality of the Qur'an includes al-inzal wa at-tanzil, hudud theory, and the distinction between the terms of the Qur'an and the Al-Kitab.